Molecular detection of Haemoproteus columbae Kruse, 1890 (Haemospororida: Haemoproteidae) in Columba livia Gmelin, 1789 (Columbiformes: Columbidae) in southern Brazil - Carolina Caetano dos Santos; Natália Soares Martins; Nilséia Feijó da Silva; Julia Somavilla Lignon; Kauê Rodriguez Martins; Oluwagbemiga Ademola Dada; Rodrigo Casquero Cunha; Fábio Raphael Pascoti Bruhn; Diego Moscarelli Pinto; Felipe Geraldo Pappen; Carolina Silveira Mascarenhas; Nara Amélia da Rosa Farias (Revista Brasileira de Parasitologia Veterinária)
Abstract The aim of this study is to describe the molecular detection of Haemoproteus columbae Kruse, 1890 (Haemospororida: Haemoproteidae) in Columba livia Gmelin, 1789 (Columbiformes: Columbidae) in southern Brazil, and to determine the prevalence of the haemosporidian by analyzing the infection in relation to birds’ age, sex, and place of origin. Blood samples were collected from 57 birds captured in the municipalities of Pelotas and Rio Grande, in the state of Rio Grande do Sul, Brazil, between May and November 2022. Microscopic examination and Polymerase Chain Reaction (PCR) based on the mitochondrial cytochrome b gene (CytB) revealed that the prevalence of the haemosporidian was 92.98% (53/57). In the sequencing analysis, the samples showed 98.87-99.08% similarity to the species H. columbae and a new lineage was recorded. No differences in infection rates were observed in relation to age, sex, or place of origin of the birds.